ANALYSIS TECNICAL AND FINANCIAL BOAT LIFT NET KM ALFIN 48 GT AT BUNGUS OCEANIC FISHING PORT (PPS BUNGUS) WEST SUMATERA PROVINCE - Fajri, Muhammad; Rengi, Pareng; Bustari, Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The purposes of research were to analyzed technical aspect of boat lift net fishing gear and to assessed economical aspects of asset, cost, revenue, and profit. To count the BCR (Benefit Cost Ratio), PPC (Payback Period of Capital) and FRR (Financial Rate of Return) for financial fishing analysis.The research was conducted in July 2018 in Bungus Oceanic Fishing Port (PPS Bungus) West Sumatera Province. The method used in this research is survey method. Primary data collection directly by involved the fishing operation and interviews with the questionnaire to get information data the financial analysis. The secondary data was collected in research-supported instantions. The result of the research shown, boat lift net fishing gear construction consists of building charts, masts, waring, waring frames, rigging and rollers. Boat Lift Net fishing gear use the ship with 21 m long and 5,5 m width. The ship use Mitsubhishi machine with power120HP to operate in the sea.The average revenue of fisherman was Rp 1.956.400.000,- with total cost Rp 1.740.950.000,- per year and profit Rp 215.450.000per year. The result of a financial analysis were BCR 1,12,- , PP 5 years and 19% for FRR. From these result, fisheries business with boat lift net fishing gear in Bungus Oceanic Fishing Port West Sumatera province  is profitable and feasible to do. Keywords : Technical Analysis; Financial Analysis; Boat Lift Net Fishing Gear; Bungus Oceanic Fishing Port